1975
DOI: 10.2134/jeq1975.00472425000400040023x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Oil Pollution of Soil on Germination, Growth and Nutrient Uptake of Corn

Abstract: The effect of crude oil pollution of soil on the growth of plants and uptake of nutrients was investigated by growing corn (Zea mays L.) on a soil polluted by crude petroleum. The levels of the crude oil application varied from 0 to 10.6% by weight of soil. Three corn crops were raised in succession, each for a period of 6 weeks, in the same soil. The yields and plant contents of N, P, K, Ca, Fe, and Mn were determined. The soil was analyzed for organic C, total and available N, extractable P, and exchangeable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
54
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(72 citation statements)
references
References 0 publications
11
54
0
Order By: Relevance
“…Crude oil which is abundantly located in the Niger Delta region of Nigeria is spilled on soil due to pipeline destruction [5]. Previous studies on crude oil pollution in soil had revealed its adverse effects on soil productivity [6,7].These studies had been majorly on the effects of pollution on chemical properties of the soil. There is therefore a need for continuous research on the problems associated with pollution resulting from spillage and the effects on the soil environment which has a negative impact on crops grown on it.…”
Section: Introductionmentioning
confidence: 99%
“…Crude oil which is abundantly located in the Niger Delta region of Nigeria is spilled on soil due to pipeline destruction [5]. Previous studies on crude oil pollution in soil had revealed its adverse effects on soil productivity [6,7].These studies had been majorly on the effects of pollution on chemical properties of the soil. There is therefore a need for continuous research on the problems associated with pollution resulting from spillage and the effects on the soil environment which has a negative impact on crops grown on it.…”
Section: Introductionmentioning
confidence: 99%
“…Plants are also susceptible to the crude oil exposure, due to phytotoxic nature of crude oil and immobilization of availability of plant nutrient in soil (Udo, and Fayemi, 1995)]. Physical, chemical and thermal methods have commonly been employed to clean up the crude oil polluted soils (Roy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Contamination of the soil by spent engine oil creates an unsatisfactory condition for life in the soil, which is due to the poor aeration it causes in the soil, immobilization of soil nutrients, loss of water-holding capacity, lowering of soil pH, and reduction in soil catalase enzyme activity (Sathiya-Moorth et al, 2008) According to Udo and Fayemi (1975) growth of plants in oil polluted soil was generally retarded and chlorosis of leaves results, coupled with dehydration of the plants indicating water deficiency. High oil concentrations in soil not only reduce the amount of water and oxygen available for plant growth (McGill,1980) but also can interfere with soil-plant-water relations through direct physical contact, (coating of root tissues) thereby adversely affecting plant growth (Baker,1971).…”
Section: Introductionmentioning
confidence: 99%